2016
DOI: 10.1016/j.str.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis for Lipid and Endotoxin Binding in RP105-MD-1, and Consequences for Regulation of Host Lipopolysaccharide Sensitivity

Abstract: MD-1 is a member of the MD-2-related lipid-recognition (ML) family, and associates with RP105, a cell-surface protein that resembles Toll-like receptor 4 (TLR4). The RP105⋅MD-1 complex has been proposed to play a role in fine-tuning the innate immune response to endotoxin such as bacterial lipopolysaccharide (LPS) via TLR4⋅MD-2, but controversy surrounds its mechanism. We have used atomically detailed simulations to reveal the structural basis for ligand binding and consequent functional dynamics of MD-1 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…One matched the bound state observed in the X-ray structure (Park et al, 2009), while in the opposite orientation the glucosamine disaccharide was rotated by 180 . The population of the latter orientation, in addition to the crystallographic state, is consistent with observations of nuclear magnetic resonance (NMR) cross-peaks for labeled endotoxin (Yu et al, 2012) and has been observed for the closely related MD-1 protein (Ortiz-Suarez and Bond, 2016). In a typical ''productive'' binding simulation, the lipid A molecule rapidly settled within the MD-2 pocket, and a native-like state was observed after $80 ns.…”
Section: Assembly Of the Lipid A/md-2 Complexsupporting
confidence: 85%
“…One matched the bound state observed in the X-ray structure (Park et al, 2009), while in the opposite orientation the glucosamine disaccharide was rotated by 180 . The population of the latter orientation, in addition to the crystallographic state, is consistent with observations of nuclear magnetic resonance (NMR) cross-peaks for labeled endotoxin (Yu et al, 2012) and has been observed for the closely related MD-1 protein (Ortiz-Suarez and Bond, 2016). In a typical ''productive'' binding simulation, the lipid A molecule rapidly settled within the MD-2 pocket, and a native-like state was observed after $80 ns.…”
Section: Assembly Of the Lipid A/md-2 Complexsupporting
confidence: 85%
“…The structural difference between MD-1 and MD-2 explains the low affinity of MD-1, which has a shallower cavity for direct binding to LPS (39). However, a recent crystallographic study demonstrates the structural basis for lipid and endotoxin binding to the CD180/MD-1 complex through a series of atomically detailed molecular simulations (40). The MD-1 cavity was expanded by a decrease in entropy to accommodate endotoxin binding, such that the CD180/MD-1 complex acts as a sink and source of LPS for TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Our microarray data showed a substantial upregulation of CD14 and downregulation of CD180 in trophoblasts exposed to calcitriol. Notably, these proteins have opposite effects on the TLR4 response (Miyake 2003, Kelley et al 2013, Ortiz-Suarez & Bond 2016. CD14 is a TLR4 co-receptor (Jersmann 2005) and is expressed in two forms, one as a GPI-linked membrane protein and one as a soluble form (sCD14) present in serum.…”
Section: Response Of Cd14 and Cd180 To Calcitriolmentioning
confidence: 99%
“…Our data extend the understanding of the vitamin D-induced innate immune responses of human trophoblast by identifying a likely role for the upregulation of CD14, and downregulation of CD180, in response to calcitriol binding to the VDR in trophoblast. These two CD proteins influence the cellular TLR4 response in opposite directions (Ortiz-Suarez & Bond 2016). TLRs are expressed in many epithelia (Gay et al 2014) including human trophoblasts, and multiple bacterial products, including LPS, activate TLR4.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation